2012
DOI: 10.1089/apc.2011.0157
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Marijuana Use Outcomes in the Healthy Choices Motivational Interviewing Intervention for HIV-Positive Youth

Abstract: Healthy Choices is a motivational interviewing intervention targeting multiple risk behaviors among HIVpositive youth. This study investigated the effects of this intervention program specifically on alcohol and marijuana use. Youth living with HIV (n = 143, mean age = 20.7, 51.5% male) were recruited from four sites in the United States, and randomly assigned to intervention or control conditions. The four-session intervention focused on two of three possible problem behaviors based on entry screening; this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 25 publications
2
42
1
2
Order By: Relevance
“…Thus, there is a robust need for the development of efficacious substance use reduction programs for this population that can be embedded within interdisciplinary care teams and delivered in a culturally and developmentally sensitive framework. Fortunately, recent research has begun to evaluate interventions such as motivational interviewing 63,64 and cognitive-behavioral therapy 65,66 to reduce the deleterious effects that substance use and psychological distress can have on adherence for YLH.…”
Section: Intervention/prevention Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a robust need for the development of efficacious substance use reduction programs for this population that can be embedded within interdisciplinary care teams and delivered in a culturally and developmentally sensitive framework. Fortunately, recent research has begun to evaluate interventions such as motivational interviewing 63,64 and cognitive-behavioral therapy 65,66 to reduce the deleterious effects that substance use and psychological distress can have on adherence for YLH.…”
Section: Intervention/prevention Programsmentioning
confidence: 99%
“…66,68,69 Fortunately, intervention researchers have started to demonstrate the feasibility of incorporating motivational interviewing and cognitivebehavioral interventions into integrated HIV youth treatment settings. 36,[63][64][65][66] However, much work is still needed in the development of such interventions to best serve the psychosocial and medical needs of young African American males living with HIV.…”
Section: Limitationsmentioning
confidence: 99%
“…Earlier published studies demonstrated that YGBM living with HIV experienced higher rates of substance use, delinquency, stigma, and discrimination, as compared to their heterosexual counterparts living with HIV. 4,5 More recently, larger multi-site quantitative studies from the Health Resources and Services Administration (HRSA) HIV/AIDS Bureau YMSM of Color SPNS Initiative and the National Institutes of Health's Adolescent Medicine Trials Network for HIV/AIDS Interventions (ATN) have been conducted to explore various patterns and predictors of sexual and substance use risk behaviors among YGBM living with HIV, [6][7][8][9][10][11] further elucidating patterns of risk among this population.…”
Section: Introductionmentioning
confidence: 99%
“…La entrevista motivacional ha probado ser eficaz en lograr un cambio de conducta en pacientes que tienen sentimientos en conflicto sobre el proceso y los resultados de dicho cambio, esto se conoce como ambivalencia (18,19,20) , y en poblaciones especiales, como las PVVS, ha demostrado mayor eficacia en la reducción de alcohol que en otras drogas (21) . A pesar de la eficacia probada del SBIRT, su implementación en el ámbito de la atención en salud ha encontrado muchas barreras, que incluyen la falta de recursos o incentivos económicos para el personal de salud por la realización de la intervención, el entrenamiento inadecuado de los proveedores, la atención inapropiada para los pacientes, la sobrecarga de trabajo, el tiempo insuficiente para la intervención (22) , y la falta de aceptabilidad de los pacientes y de los proveedores (23,24) .…”
Section: Introductionunclassified